At first sight - Sparks, Nicholas (New York : Warner Books, 2005)
Happily married and anticipating the birth of his first child, Jeremy Marsh receives a mysterious message that reopens wounds from the past and changes the course of his marriage.
Accelerated Reader AR
Keywords: Married people -- Fiction; Pregnant women -- Fiction; North Carolina -- Fiction; Suspense fiction